2014
DOI: 10.1002/jrs.4512
|View full text |Cite
|
Sign up to set email alerts
|

Gem quality and archeological green ‘jadeite jade’ versus ‘omphacite jade’

Abstract: Raman spectroscopy was used for the characterization of seven gem quality green ‘jade’ samples and three green ‘jade’ samples of archaeological importance. The results were also compared with those acquired by other nondestructive techniques such as classical gemology, energy‐dispersive X‐ray fluorescence (EDXRF), ultraviolet‐visible‐near infrared (UV‐Vis‐NIR) in absorption, Fourier transform infrared spectroscopy (FTIR) in absorption and micro‐FTIR in reflectance. Five samples of gem quality and two samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…Raman spectroscopy can identify different species of pyroxenes and can detect order-disorder transitions. 10,12,25,26 For pyroxene, the Raman spectral wavenumber in the band of 950-1200 cm À1 is caused by Si-O non-bridging and bridging stretching vibrations, which are mainly related to the Si-O nb mode; the wavenumber of the Si-O b -Si stretching vibration can be assigned to the range of 650-750 cm À1 , and the position depends on the bond angle and the cation type of M 2 . The band of 500-590 cm À1 is caused by the bending vibration of O-Si-O in the silicon oxygen tetrahedron.…”
Section: Jadeite Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy can identify different species of pyroxenes and can detect order-disorder transitions. 10,12,25,26 For pyroxene, the Raman spectral wavenumber in the band of 950-1200 cm À1 is caused by Si-O non-bridging and bridging stretching vibrations, which are mainly related to the Si-O nb mode; the wavenumber of the Si-O b -Si stretching vibration can be assigned to the range of 650-750 cm À1 , and the position depends on the bond angle and the cation type of M 2 . The band of 500-590 cm À1 is caused by the bending vibration of O-Si-O in the silicon oxygen tetrahedron.…”
Section: Jadeite Phasementioning
confidence: 99%
“…The symmetry is reduced to P2/n. [10][11][12][13] It is difficult to distinguish jadeite from omphacite under a polarizing microscope, because of their similar optical characteristics, which need to be combined with multiple testing methods for analysis. Common analytical techniques employed in the study of jadeite materials are petrography, X-ray powder diffraction (XRD), Raman spectroscopy, and electron probe microanalysis (EPMA).…”
Section: Introductionmentioning
confidence: 99%
“…L'analyse cartographique doit en efet prendre en considération la nature différente des objets étudiés ain de distinguer des particularités chronologiques ou régionales (Renfrew, 2005). Les critères choisis sont les matières premières (en privilégiant le système d'opposition prévalent durant le V e millénaire : roches sombres -éclogites et omphacitites versus roches claires -jadéitites et certaines omphacitites - Pétrequin, Sheridan et al, 2011, Coccato et al, 2013 et l'origine (massif du Mont Viso versus massif du Mont Beigua, Pétrequin, Errera et al, 2012c), l'appartenance typologique (Pétrequin, Sheridan et al, 2008 ;Pétrequin, Cassen et al, 2012b), le degré de inition, la lon-ArcheoSciences, revue d'archéométrie, 41(1), 2017, p. 7-23 gueur des pièces complètes (Pétrequin, Cassen et al, 2012b) et le contexte de découverte . Les répartitions doivent être comparées selon ces multiples critères et, dans la mesure du possible, en les combinant.…”
Section: Objectifs Et Méthodesunclassified
“…Coccato et al . characterised seven gem quality green ‘jade’ samples and three green jade samples of archaeological importance by application of Raman spectroscopy.…”
Section: Raman Spectroscopy In Paleontology and Prehistoric Artmentioning
confidence: 99%
“…Coccato et al [41] characterised seven gem quality green 'jade' samples and three green jade samples of archaeological importance by application of Raman spectroscopy. The results showed that five samples of gem quality and two samples of archaeological interest were 'jadeite jade', while two samples of gem quality and one sample of archaeological interest were found to be 'omphacite jade'.…”
Section: Raman Spectroscopy In Paleontology and Prehistoric Artmentioning
confidence: 99%